Nilai Budaya pada Lirik Lagu Nyanyian Onang-onang Suku Batak Mandailing (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research aims to describe the cultural values ​​reflected in the lyrics of the Onang-onang songs of the Mandailing Batak tribe. Malikussaleh University Indonesian Language Education Study Program, 2024. The method used is descriptive qualitative. Data collection techniques in this research are interview techniques, listening and observing techniques. The data used in this research are the lyrics of the Onang-onang songs of the Mandailing Batak tribe which contain cultural values. The data sources for this research were 4 people from the Mandailing Batak tribe. Data analysis in this research is data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it was found that 38 cultural values ​​were reflected in the lyrics of the Onang-onang songs of the Mandailing Batak tribe. The cultural values ​​in the lyrics of the Onang-onang songs of the Mandailing Batak tribe are divided into 5 types of cultural values. (1) the nature of human life was found in 8 data, (2) the nature of human work was found in 9 data, (3) the nature of human time was found in 9 data, (4) the relationship between humans and nature was found in 1 data, (5) the relationship with humans 11 data were found.